Mechanisms of ACL injury in professional rugby union: a systematic video analysis of 36 cases - Montgomery, C.; Blackburn, J.; Withers, D.; Tierney, G.; Moran, C.; Simms, C. (British Journal of Sports Medicine, 2018)
Background: The mechanisms of ACL injury in rugby are not well defined.